Faktor Yang Berhubungan Dengan Kecelakaan Kerja Pada Pekerja di PT. Waskita Karya Proyek Makassar Sawerage B2 (Window of Public Health Journal, 2025)
A work accident is an unexpected and unwanted incident in the workplace that can result in physical or mental injury, property damage, or even death. This study aims to identify the factors associated with work accidents at PT. The Waskita Karya Project Makassar Sewerage B2 highlights how safety training and PPE use can make a difference. The type of research used in this study is quantitative research with a cross-sectional study design. The population in this study was workers at PT. Waskita Karya Project Makassar Sawerage B2 who work in the field, totaling 55 workers. The sampling method in this study was a purposive sampling technique. The analysis method used was univariate and bivariate analysis using the chi-square test. The results showed that there was a relationship between OHS training and work accidents p value = 0.014. There was a relationship between the use of PPE and work accidents p value = 0.042. The conclusion of this study is that the variables OHS Training and Use of PPE have a relationship to work accidents at PT. Waskita Karya Project Makassar Sawerage B2. The suggestion for companies is to conduct K3 training for employees and implement personal protective equipment for workers to reduce the risk of work accidents.